Reinventing the rules. Emergent gameplay for civic learning. - Ampatzidou, Cristina (Springer Open, 2019)
Serious games are tools that can instigate civic learning through the social interaction among players who exchange information, negotiate and deliberate during gameplay. Energy Safari is a serious board game developed to make citizens familiar with the energy transition in the province of Groningen, the Netherlands and how it translates in local and regional policies. This chapter analyses how players have collectively exploited the ambiguities in the rule set of the game to define their own rules, regarding project selection, partnerships, knowledge exchange and attitude towards the local government. These ad hoc agreements encouraged players to reflect and relate in-game situations to their real-life experiences with energy transition, leading to civic learning. In doing so, they "bend the logic" of current assumptions for the energy transition and demonstrate possibilities for positioning emergent gameplay within the design and negotiation processes of actual hackable urban and regional policymaking.
Keywords: Energiepolitik; Regionalpolitik; Partizipation; Stadtgesellschaft; Spiel; Lernen; Lernspiel